Comparative anti-proliferative activity of some new 2-(arylazo)phenolate–palladium (II) complexes and cisplatin against some human cancer cell lines. (March 2015) - Banerjee, P.; Majumder, P.; Halder, S.; Drew, M. G. B.; Bhattacharya, S.; Mazumder, S.
Abstract: In this study, we report the synthesis of four 2-(arylazo)phenol–Pd(II) complexes and their anti-proliferative property against the human lung cancer (A549), cervical cancer (HeLa), and ovarian teratocarcinoma (PA-1) cell lines with cisplatin as the gold standard. One of the complexes, [Pd(L 2 )2 ], induced robust apoptosis in all the chosen cells, as revealed by annexin-V-positive/propidium iodide dual staining, increased sub-G1 cell cycle population, and significant morphological changes in the treated cells. The Pd complex inflicted mitochondrial dysfunction leading to mitochondrial membrane potential loss, reactive oxygen species generation and release of cytosolic cytochrome c that activated caspase-9 and caspase-3 proteins which finally caused programmed cell death.